Do Couples Bargain over Fertility? Evidence Based on Child Preference Data - Timo Hener (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Empirical literature has found evidence in favor of household bargaining models. In contrast to earlier tests that are limited to assignable private goods, we use child preference data in order to extend the empirical evidence on household bargaining to public household goods. In the empirical analysis, we exploit the different theoretical predictions for couples with heterogeneous and homogeneous preferences derived from household models. Our results indicate that couples bargain over fertility. Furthermore, we find that the ability to commit to household resource allocations depends on the gender of the partner with higher preferences.
Keywords: 330; Familienplanung; Verhalten; Offenbarte Präferenzen; Verhandlungstheorie; Haushaltseinkommen; Familienleistungsausgleich; Familienökonomik; Fertilität; Theorie